Fatigue strength of circular and rectangular hollow sections subjected to complex loading conditions - Lie, Seng Tjhen. (2009)
In order to understand the fatigue growth behaviors of tubular joints, large-scale tubular joint fatigue tests had been performed for a number of decades. But most of them were tested under basic loading, i.e. axial load (AX), in-plane-bending (IPB) and out-of-plane (OPB). In the current test program, full-scale circular hollow sections (CHS) and rectangular hollow sections (RHS) tubular joints were tested under the basic and combined loading so as to understand their fatigue crack growth behaviors as well as their fatigue strengths. The tests in this research project include experimental stress analyses under basic and combined loading and fatigue tests under basic and combined loading. The static tests were carried out first to determine the stress concentration factors (SCFs) of the joints, and the peak hot spot stress (HSS) locations where the cracks may initiate. The SCF results are also used to compare with some of the well-established existing SCF equations. In the past decades, many tests on tubular joints had been performed (van Delft et al., 1986; Ritchie et al., 1989; Myers, 1998 etc.), but the 3D crack shapes formed during propagation were scarcely captured in these fatigue tests. Therefore, it is difficult to model the accurate crack surface in finite element models which may produce inaccurate stress intensity factors solution. In order to validate the stress intensity factors along the crack front of the tubular joints for the next phase of the research project, fatigue tests were carried out whereby the 3D crack propagation and profiles were monitored using the Alternating Current Potential Drop (ACPD) technique, and hence the fatigue strengths of these specimens.